In silico analysis of the profilaggrin sequence indicates alterations in the stability, degradation route, and intracellular protein fate in filaggrin null mutation carriers - Paul, Argho Aninda; Szulc, Natalia A.; Kobiela, Adrian; Brown, Sara J.; Pokrzywa, Wojciech; Gutowska-Owsiak, Danuta (Frontiers in Molecular Biosciences, 2023)
Background: Loss of function mutation in FLG is the major genetic risk factor for atopic dermatitis (AD) and other allergic manifestations. Presently, little is known about the cellular turnover and stability of profilaggrin, the protein encoded by FLG. Since ubiquitination directly regulates the cellular fate of numerous proteins, their degradation and trafficking, this process could influence the concentration of filaggrin in the skin. Objective: To determine the elements mediating the interaction of profilaggrin with the ubiquitin-proteasome system (i.e., degron motifs and ubiquitination sites), the features responsible for its stability, and the effect of nonsense and frameshift mutations on profilaggrin turnover. Methods: The effect of proteasome inhibition on the expression of profilaggrin and processed products was assessed by immunoblotting. Wild-type profilaggrin sequence and its mutated variants were analysed in silico using the DEGRONOPEDIA and Clustal Omega tool. Results: Proteasome inhibition stabilizes profilaggrin and its high molecular weight derivatives. In silico analysis of the sequence determined that profilaggrin contains 18 known degron motifs as well as multiple canonical and non-canonical ubiquitination-prone residues. FLG mutations generate products with increased stability scores, altered usage of the ubiquitination marks, and the frequent appearance of novel degrons, including those promoting C-terminus-mediated degradation routes. Conclusions: The proteasome is involved in the turnover of profilaggrin, which contains multiple degrons and ubiquitination-prone residues. FLG mutations alter those key elements, affecting the degradation routes and the mutated products’ stability.